2016
DOI: 10.1016/j.jplph.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Legume nodules from nutrient-poor soils exhibit high plasticity of cellular phosphorus recycling and conservation during variable phosphorus supply

Abstract: Nitrogen fixing legumes rely on phosphorus for nodule formation, nodule function and the energy costs of fixation. Phosphorus is however very limited in soils, especially in ancient sandstone-derived soils such as those in the Cape Floristic Region of South Africa. Plants growing in such areas have evolved the ability to tolerate phosphorus stress by eliciting an array of physiological and biochemical responses. In this study we investigated the effects of phosphorus limitation on N 2 fixation and phosphorus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 52 publications
(63 reference statements)
0
11
1
Order By: Relevance
“…Available literature showed that environmental stimuli could alter lipid content and lipid metabolism in higher plants. For instance, the content of polar lipid compounds in Arabidopsis and Virgilia divaricata was decreased by UV-B radiation [80], heat stress [83], P deficiency [84] and high light [14]. Moreover, RNA-Seq and proteomic studies showed that the genes or functional proteins involved in lipid metabolism could be altered by salinity stress in barley [85], low temperatures in cassava [86], P deficiency in Arabidopsis [87], boron deficiency in C. sinensis [63], and Mg deficiency in C. reticulata [19] and C. sinensis leaves [88].…”
Section: Discussionmentioning
confidence: 99%
“…Available literature showed that environmental stimuli could alter lipid content and lipid metabolism in higher plants. For instance, the content of polar lipid compounds in Arabidopsis and Virgilia divaricata was decreased by UV-B radiation [80], heat stress [83], P deficiency [84] and high light [14]. Moreover, RNA-Seq and proteomic studies showed that the genes or functional proteins involved in lipid metabolism could be altered by salinity stress in barley [85], low temperatures in cassava [86], P deficiency in Arabidopsis [87], boron deficiency in C. sinensis [63], and Mg deficiency in C. reticulata [19] and C. sinensis leaves [88].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, P homeostasis in nodules is important. Over time, legumes have evolved mechanisms to maintain P homeostasis in nodules, including enhanced Pi translocation from host roots, direct P uptake from growth media by nodules and increased recycling of P via APase activity in nodules (Vardien et al , , Sulieman and Tran ). It has already been reported that acid phosphatase activity significantly increases in nodules under P‐limited conditions (AraĂșjo et al , Sulieman and Tran ).…”
Section: Discussionmentioning
confidence: 99%
“…may be affected positively in response to an adequate P nutrition that has positive consequences on robust root systems, vigorous seedlings, ammonium assimilation into amino acids, and ureides, as well as synthesis of mitochondrial and symbiosome membranes for functional NF nodules ( Fageria et al, 1995 ; Schachtman et al, 1998 ; Nyoki and Ndakidemi, 2014a ; Tairo and Ndakidemi, 2014 ; Sulieman and Tran, 2015 ). This is of particular importance for NF legumes whose nodule formation, nodule functioning, and the energy costs related to NF greatly depend on the P status in plant and nodule tissues ( Vardien et al, 2016 ). Moreover, the fact that root-nodules are strong P sinks, with nodule P concentrations often exceeding those of roots and shoots also indicates the important role of P in the legume symbiosis processes ( Schulze and Drevon, 2005 ; Bargaz et al, 2012 ; Nyoki and Ndakidemi, 2014a ).…”
Section: Microbially-mediated N and P In Soilsmentioning
confidence: 99%